Analysis of Characteristics of 2G/3G Cellular Networks in rural and urban areas of Delhi (International Journal of Engineering and Computer Science, 2017)
Recent years India has experienced significant growth in cellular penetration and it is the second largest and fastest growing mobile market in the world according to recent report by the Telecom Regulatory Authority of India. In this paper illustration of cellular data networks available in India is done. Throughput latency, Availability and other network characteristics of five cellular service providers (Idea, BSNL, Reliance, MTNL and Airtel) across six locations are evaluated and a robust, scalable, and extensible suite to conduct active client side measurements in rural regions is designed. Variety of tests has been done over 90 days by measuring the following key insights about the cellular data and understanding of such network parameters and their impact on performance will help to explore the strategies for optimizations at end-hosts as well as within the service provider network.